A vision to the future: value-based laboratory medicine - Plebani, Mario; Cadamuro, Janne; Vermeersch, Pieter; Jovičić, Snežana; Ozben, Tomris; Trenti, Tommaso; McMillan, Brian; Lowe, Christopher R.; Lennerz, Jochen; Macintyre, Elizabeth; Gabelli, Carlo; Sandberg, Sverre; et al. (Clinical chemistry and laboratory medicine, 2024)
The ultimate goal of value-based laboratory medicine is maximizing the effectiveness of laboratory tests in improving patient outcomes, optimizing resources and minimizing unnecessary costs. This approach abandons the oversimplified notion of test volume and cost, in favor of emphasizing the clinical utility and quality of diagnostic tests in the clinical decision-making. Several key elements characterize value-based laboratory medicine, which can be summarized in some basic concepts, such as organization of in vitro diagnostics (including appropriateness, integrated diagnostics, networking, remote patient monitoring, disruptive innovations), translation of laboratory data into clinical information and measurable outcomes, sustainability, reimbursement, ethics (e.g., patient empowerment and safety, data protection, analysis of big data, scientific publishing). Education and training are also crucial, along with considerations for the future of the profession, which will be largely influenced by advances in automation, information technology, artificial intelligence, and regulations concerning in vitro diagnostics. This collective opinion paper, composed of summaries from presentations given at the two-day European Federation of Laboratory Medicine (EFLM) Strategic Conference “A vision to the future: value-based laboratory medicine” (Padova, Italy; September 23-24, 2024), aims to provide a comprehensive overview of value-based laboratory medicine, projecting the profession into a more clinically effective and sustainable future.
Gesehen am 18.03.2025